Pandangan Ekonomi Syariah Atas Pengaruh Ekuitas Merek, Harga, Dan Distribusi Terhadap Trend Keputusan Pembelian Rokok Elektrik (Studi Pada Mahasiswa Di Kota Palangka Raya) - Akbar, Wahyu; Wulansari, Septiana (CV. ITTC INDONESIA, 2022)
The purpose of this study was to determine the effect of brand equity, price, and distribution on purchasing trends, especially e-cigarettes among students, which was then reviewed from the perspective of Islamic economics. This research uses quantitative research. The population is students who use e-cigarettes with a sample of 233 respondents. The analysis technique used is normality test, linearity test, heteroscedasticity test, multiple linear regression test, product moment test, determinant coefficient (r2), simultaneous significant test (F test), partial significant test (T test). The analysis of this study uses the SPSS 16.0 application and also uses a contextual approach to Islamic economics and phenomenology. The results of this study indicate that what is obtained from the F test has a significant effect, which is 107.056. Partial t-test results on purchasing decisions have a significant effect, namely brand equity of 7,971, price of 5,304, distribution of 2,302. Based on the results of multiple regression analysis, the brand equity variable has a more dominant influence on purchasing decisions because the regression equation is 0.402. Islamic economics views the trend of purchasing decisions among students as there needs to be awareness of consumption that is oriented towards maslahah. The content of mashlahah consists of 2 things, namely the benefits and blessings that should exist in brand equity, price, and distribution.